(untitled) (Nordic Journal of African Studies, 2009)
Senegal is a multiethnic country where there are around 20 communities speaking 25 languages. The Wolof community is the largest (42.7%) and its language is the lingua franca in the country. However, fieldwork in Senegal found out perceptible signs of the corrosion of the attitudes of Senegalese people toward the Wolof speech community which are disturbingly less positive than one would expect. For instance, 27% of the respondents (N=404) rated the Wolof people as dishonest, 38% viewed them as insincere, 33% perceived them as lazy, and 43% rated them as unreliable. This paper examines attitudes toward speech communities in Senegal, namely Wolof, the mother tongues, French and English. It argues that language policy in Senegal should focus on fostering positive attitudes if the Wolof language is to be given the status and the roles it aspires.